PERAN GURU PENGGERAK DALAM MENINGKATKAN PROFESIONALISME REKAN SEJAWAT DI SMA NEGERI 3 PANYABUNGAN - Siti Fatimah; Faisal Musa; Marwah Marwah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to explore the strategies used by mobilizing teachers to enhance the professionalism of their colleagues at SMA Negeri 3 Panyabungan, the forms of their roles, as well as the efforts made to minimize the inhibiting factors and maximize the supporting ones in improving teacher professionalism. The research employed a qualitative method with a descriptive approach. Informants were selected using purposive sampling and included mobilizing teachers, fellow non-mobilizing teachers, and the principal of SMA Negeri 3 Panyabungan. Data were collected through interviews, observations, and documentation. The validity of the data was ensured using triangulation techniques. The findings of the study are as follows: (1) The strategies used by mobilizing teachers to improve the professionalism of their colleagues include providing assistance through coaching and mentoring, collaboration, and teamwork. (2) the roles of teacher mobilizers include acting as facilitators of teacher learning communities, promoting a culture of reflection, enhancing teacher collaboration, and guiding fellow teachers in driving educational change and improving professionalism, (3) To minimize the inhibiting factors, mobilizing teachers take a personal approach and demonstrate the tangible benefits of the applied learning innovations, helping unmotivated teachers become more open to adopting new teaching methods.